Routine Radiochemical Quality Control of 99mTc eluate and 99mTc-Labeled Radiopharmaceuticals - Islam, Md Saiful; Azim, Mohammad Anwar-Ul; Uddin, Md Jashim; Biswasarma, Sanchoy Chandra; Islam, Sanjida; Banu, Most Layla Saroware; Mia, Md Shohag; Mehdi, Hasan; Siddiquee, Nur E Alam; Kadir, Muhtasim (Bangladesh Journal of Nuclear Medicine, 2024)
Technetium-99m (99mTc)-labeled radiopharmaceuticals are indispensable tools in nuclear medicine, playing a vital role in various diagnoses such as myocardial perfusion imaging (MPI), bone scintigraphy, thyroid imaging, renal scintigraphy, lung perfusion and ventilation scans, gastrointestinal imaging, parathyroid imaging, tumor imaging, etc. Quality control plays a key role in ensuring the safety and efficacy of radiopharmaceuticals, particularly in the case of radiopharmaceuticals. The production of Tc-99m-labeled radiopharmaceuticals involves a complex series of steps, from generator elution to final patient administration. The Nuclear Regulatory Commission (NRC), United States Pharmacopeia and National Formulary (USP-NF), British Pharmacopeia (BP), and European Pharmacopeia (EP) limit the amount of radionuclide contamination allowed in 99m Tc solutions for patient use. Various methods have been used to ensure the quality of the 99mTceluate. The radiochemical purity of various 99m Tc radiopharmaceuticals is checked by Instant Thin Layer Chromatography (ITLC), and radio-nuclide identity was confirmed by obtaining a gamma spectrum from a High Purity Germanium (HPGe) detector and measuring the half-life of the radiopharmaceuticals. pH and sterility testing are also performed before administration to the patient’s body. These QC methods collectively help verify the quality and safety of 99mTc radiopharmaceuticals, ensuring that they meet the necessary standards for clinical use and patient care as per IAEA guidelines. Bangladesh J. Nuclear Med. 26(2): 193-197, 2023